Addressing Islamic Values in Medical Imaging Professionalism - Muhamad Ruzlan, Siti Maryam; Zainuddin, Zainul Ibrahim (IIUM Medical Journal Malaysia, 2018)
This paper presents a conceptual framework in aligning the integration of Islamic values into the Medical imaging practices through the aspect of Islamic Personality (IP). IP is a form of moral quality in the psychological aspects of a human, which is governed by the belief in Allah as the One God and Prophet Muhammad (Peace be upon him) as His servant and His messenger. This work is seen within the context of harmonizing Islamic values to the currently accepted professional attributes in medical imaging. The medical imaging practice is comprised of various domains; basic principles in healthcare and medical imaging, patient care, use of technology, the technicalities or procedures, quality, safety, economic, research and professionalism. In order to conceptualize the IP as applicable for Muslim Medical imaging practitioners’ ten professional guidelines were examined. The extracted professional attributes were sorted into common themes within the context of the above domains. From the examination of the guidelines, the expected professional attributes of medical imaging practitioners are closely related to the concepts in Islamic ethics (‘ilm al-akhlaq) and circle around character building. There are nineteen common professional personality traits that were determined from the Medical imaging professional guidelines; 1) respectful, 2) safe practice, 3) safe activity, 4) equality, 5) trustworthy, 6) honesty and integrity, 7) truthful, 8) responsible and accountable, 9) compassionate, 10) wisdom, and 11) being up-to-date, 12) competence, 13) teamwork, 14) self-reflection, 15) dignity, 16) ethical behaviors, 17) adhere to laws and regulations, 18) effective communication, and 19) continuity of knowledge and skills development. Some of these traits were interpreted within the Islamic perspectives as applicable for Muslim Medical imaging practitioners. The outlined conceptual framework could be a model for improvement in the practice of Muslim Medical imaging practitioners in terms of IP. In conclusion, the professional attributes as addressed in the current professional guidelines are feasible to be aligned with the IP to form a set of Islamic personalities that are applicable for Muslim Medical imaging practitioners.